Effect of Phase Change Materials on Temperature and Moisture Distributions in Clothing during Exercise in Cold Environment (Journal of Fiber Bioengineering and Informatics, 2018)
This paper reports a study on the effect of phase change material (PCM) in design of coldprotective clothing. Two clothing systems with the same structural design, one was smart clothing(clothing C) was treated with PCM, the other one was moisture management clothing (clothingB), were tested in a climate chamber where was controlled at -15&#176C. Eleven young male studentsvolunteered to take part in wear trial experiments. The experimental results showed that the ear canaltemperature when subjects wearing clothing treated with PCM was significantly higher that whensubjects wearing moisture management clothing. The results also indicated that subjects wearing theclothing treated with PCM felt more comfortable than wearing the clothing untreated with PCM.
Keywords: PCM; cold protective clothing; cold environment; temperature distribution; humidity distribution